Why should stakeholders consider the effect of tensions in collaborative innovation in healthcare-lessons learned from surveying integrated care projects in Germany - Malte Haring; Juliane Schiller; Martin Gersch; Volker Amelung (BMC, 2023)
Abstract Introduction The German Innovation Fund supports projects that aim to improve healthcare through integration and intersectoral collaboration. As is typical for collaborative innovation projects, partners often pursue different objectives, which can create tensions and affect outcomes. The study aims to explore the causes and effects of tensions in integrated care projects and how frameworks, processes, and management should be designed to deal with tensions and achieve their productive effects. Methods In an online survey we asked participants about the causes, effects, and management of tensions and their implications for integrated care projects (n = 58 completed questionnaires). We applied bivariate descriptive statistics to analyse the quantitative data. Results Tensions between stakeholders, caused by deep-seated differences and the design of the project frameworks, often affect the course and outcome of innovative integrated care projects. However, through appropriate conflict management and negotiation processes such tensions can be managed constructively and lead to better outcomes. Discussion Tension is usually seen as something unpleasant to be avoided and/or overcome. In fact, tensions can have positive effects, the importance of which remains little understood. Developing appropriate frameworks for managing and integrating different perspectives are key factors in unlocking the positive potential of tensions in integrated care projects.